1991
DOI: 10.1007/bf02403952
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of optical recording on thin films of quaternary glasses Cu-As-Se-I

Abstract: The characteristics of optical recording and changes in the hologram parameters of the amorphous quaternary system Cu-As-Se-I are described. The dependence of the relative contrast of recording on the exposure and transparency properties of the film before and after erasure is the basis for discussion of these processes. Investigation into the dependence of diffraction efficiency of the holograms indicates that these quantities are determined by the thin film composition. IntroductionSome amorphous semiconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Some previous investigations [4][5][6] have shown that the introduction of Cu into the As 2 Se 3 glass causes a substantial increase in the efficiency (contrast, photosensitivity, reversibility and diffractive efficiency) of optical recording on thin films of Cu x (As 2 Se 3 ) 100−x , x < 20 at.%. It can be supposed that the Cu atoms interacting with Se atoms produce an additional number of weak As-Se bonds and weak As 'dangling' bonds, which are responsible for the process of optical recording.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous investigations [4][5][6] have shown that the introduction of Cu into the As 2 Se 3 glass causes a substantial increase in the efficiency (contrast, photosensitivity, reversibility and diffractive efficiency) of optical recording on thin films of Cu x (As 2 Se 3 ) 100−x , x < 20 at.%. It can be supposed that the Cu atoms interacting with Se atoms produce an additional number of weak As-Se bonds and weak As 'dangling' bonds, which are responsible for the process of optical recording.…”
Section: Introductionmentioning
confidence: 99%
“…͑1͒, and ph is the characteristic phonon frequency taken as 10 12 Hz, a typical value in amorphous materials. ͑1͒, and ph is the characteristic phonon frequency taken as 10 12 Hz, a typical value in amorphous materials.…”
Section: Source Characterizationmentioning
confidence: 99%
“…1 Moreover, ChG glasses are conducive for use in fiber optics and integrated optics since they have many unique optical properties and exhibit a good transparency in the infrared region. Some previous investigations 12 have shown that the introduction of Cu into the As 2 Se 3 glass causes a substantial increase in the efficiency ͑contrast, photosensitivity, reversibility, and diffractive efficiency͒ of optical recording on thin films of Cu x ͑As 2 Se 3 ͒ 100−x with x Ͻ 20 at. 9 As 2 S 3 and As 2 Se 3 have traditionally been used for mid-IR fibers with transmission windows up to 12 m. In order to further the transmission window into the far-IR range ͑Ͼ15 m͒, the S or Se atoms, which cause far-IR absorption due to As-S or As-Se bond vibration, can be replaced by heavier counterparts such as Te or transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…The chalcogenide glass film based registering media have unique properties, such as amorphous structure, high chemical resistivity, and a wide range of spectral sensitivity. There are numerous potential applications in microelectronics, high-density information recording, holography [8][9][10], and other areas.…”
Section: Introductionmentioning
confidence: 99%